Cardiac Tamponade as the Initial Presentation of Coexistent Systemic Lupus Erythematosus and Addison’s Disease: A Case Report and Literature Review - Abdullah Abu Keshek MD; Mohammad Hakam Shehadeh MD; Mohammed M. Salahaldin MD; Salem K. Qupp MD; Omar Mohammad Marouf MD; Ahmad A. Dallashi MD (Journal of Investigative Medicine High Impact Case Reports)
Cardiac tamponade is a rare presentation of systemic lupus erythematosus (SLE), occurring in less than 1% of cases. Its coexistence with primary adrenal insufficiency (Addison’s disease) represents an even rarer clinical scenario. We present the case of a 28-year-old female who presented with cardiac tamponade as the initial presentation of concurrent SLE and Addison’s disease. Laboratory investigations revealed positive antinuclear and anti-dsDNA antibodies, low complement levels, hyponatremia, and hyperkalemia. Adrenal function tests confirmed primary adrenal insufficiency. Echocardiography identified a large pericardial effusion with cardiac tamponade, necessitating emergent pericardiocentesis. The patient responded well to high-dose glucocorticoids, hydroxychloroquine, and mineralocorticoid replacement therapy. This case highlights the rare and challenging presentation of cardiac tamponade as the initial presentation of the coexistent SLE and Addison’s disease. Prompt recognition and management of this complex scenario are crucial. Clinicians should maintain a high index of suspicion for underlying autoimmune disorders in patients presenting with cardiac tamponade.